Pengaruh Model Pembelajaran VCT (Value Clarification Technique) Terhadap Keterampilan Berbicara Siswa Kelas IV SD Inpres Talakauwe Kecamatan Bajeng Barat Kabupaten Gowa - Dewi Rahayu; Andi Adam; Besse Syukroni (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to determine the significant effect of implementing the VCT learning model on the speaking skills of class IV students at SD Inpres Talakauwe, West Bajeng District, Gowa Regency. The type of research used in this research is pre-experimental and is a quantitative type of research. The sample in this study was 25 students. Data collection techniques were carried out using learning results tests and observation sheets. Data analysis of research results was obtained from descriptive statistical data analysis and inferential data analysis. The research results showed that speaking skills before implementing the VCT (Value Clarification Technique) learning model in the pretest had an average score of 64. Meanwhile, in the posttest it had improved with an average score of 83.2. The results of the t-test analysis regarding the influence of the VCT (Value Clarification Technique) learning model on the learning outcomes of student participants show that the significance value obtained is good, namely the influence of the VCT (Value Clarification Technique) learning model on speaking skills (Sig = 0.001) is smaller than the value The alpha set is 0.05 (0.001 < 0.05). Based on the results obtained, it can be concluded that Ho is rejected and H1 is accepted, which states that there is an influence of the use of the VCT (Value Clarification Technique) learning model on the speaking skills of class IV students at SD Inpres Talakauwe, West Bajeng District, Gowa Regency.